PROBLEMS WITH CORRECT PRONUNCIATION OF ENGLISH WORDS AND THEIR SOLUTION (Academicia Globe: Inderscience Research, 2022)
We know that words in all languages are different and have different pronunciations. Just as we pronounce words in our own language, words in other languages cannot be pronounced in our own way because they are read, written, and pronounced differently in all languages. Every language has reading rules. No matter what language we are learning, before memorizing words, we need to learn grammar or word reading rules after recognizing the letter. Learners of English also face difficulties in reading and pronouncing words. This article highlights the pronunciation of English learners and provides feedback on how to pronounce words correctly in English.